The Emerging Role of T Cell Ig Mucin-1 (TIM-1) in The Mechanism of Liver Ischemia and Reperfusion Injury - Uchida, Yoichiro (2010)
The TIM (T cell Immunoglobulin and Mucin domain-containing molecules) protein family, expressed by T cells, plays a crucial role in regulating host adaptive immunity and tolerance. However, its role in local inflammation, such as innate immunity-dominated organ ischemia and reperfusion injury (IRI) remains unknown. Liver IRI occurs frequently after major hepatic resection or liver transplantation. Using an antagonistic anti-TIM-1 Ab, we studied the role of TIM-1 signaling in the model of partial warm liver ischemia followed by reperfusion. Anti-TIM-1 Ab monotherapy ameliorated the hepatocellular damage and improved liver function due to IR, as compared to controls. Histological examination has revealed that anti-TIM-1 Ab treatment decreased local neutrophil infiltration, inhibited sequestration of T lymphocytes, macrophages, TIM-1 ligand expressing TIM-4+ cells, and reduced liver cell apoptosis. Intrahepatic neutrophil activity and induction of pro-inflammatory cytokines/chemokines were also reduced in the treatment group. In parallel in-vitro studies, anti-TIM-1 Ab suppressed IFN-γ production in Con A-stimulated spleen T cells, and diminished TNF-α/IL-6 expression in macrophage/spleen T cell co-culture system. This is the first study, which provides evidence for the novel role of TIM-1 signaling in the mechanism of liver IRI. TIM-1 regulates not only T cell activation but may also affect macrophage function in the local inflammation response. These results provide compelling data for further investigation of TIM-1 pathway in the mechanism of IRI, to improve liver function, expand the organ donor pool, and improve the overall success of liver transplantation.